Interventions to increase utilisation of advanced care planning documentation for hospitalised older adults - Laura E Walker; Anne Liwonjo; Deepi G Goyal (BMJ Open Quality)
Objective Understanding patients’ wishes and preferences during hospitalisation is a crucial component of care. We identified a gap related to documentation of advance directives and patient preferences for care and focused on ensuring appropriate goals of care discussions were occurring and documented. Our aim was to improve the documentation of advance care planning notes to include 80% of targeted hospitalised patients.Patients and methods Hospitalised patients in two community hospitals were included. We performed serial Plan-Do-Measure-Act cycles. The first intervention introduced the ‘surprise question’ during an afternoon huddle. Intervention 2 emphasised documentation of the advance care planning note. The third intervention used a structured approach led by administrators at daily multidisciplinary huddles and identified patients with an Elderly Risk Assessment score of 16 or greater as targets for advance care planning documentation.Results From a baseline performance under 10%, we increased to greater than 80% of patients with Elderly Risk Assessment scores of 16 or higher having documented advance care planning. We were able to sustain this performance over subsequent years.Conclusion A structured approach that identifies a targeted population at higher risk of mortality, and implementation of a checklist at a daily multidisciplinary huddle provided sustained improvement in advance care planning documentation. This provides the opportunity for improved patient care that is aligned with their values and preferences.